Residential Segregation and Infant Mortality: A Multilevel Study Using Iranian Census Data - SS Hashemi Nazari; M Mahmoodi; MA Mansournia; K Holakouie Naieni (Tehran University of Medical Sciences, 2012)
Background: There is a great amount of literature concerning the effect of racial segregation on health outcomes but few papers have discussed the effect of segregation on the basis of social, demographic and economic characteristics on health. We estimated the independent effect of segregation of determinants of socioeconomic status on infant mortality in Iranian population. Methods: For measuring segregation, we used generalized dissimilarity index for two group and multi group nominal variables and ordinal information theory index for ordinal variables. Sample data was obtained from Iranian latest national census and multilevel modeling with individual variables at level one and segregation indices measured at province level for socioeconomic status variables at level two were used to assess the effect of segregation on infant mortality. Results: Among individual factors, mother activity was a risk factor for infant mortality. Segregated provinces in regard to size of the house, ownership of a house and motorcycle, number of literate individual in the family and use of natural gas for cooking and heating had higher infant mortality. Segregation indices measured for education level, migration history, activity, marital status and existence of bathroom were negatively associated with infant mortality. Conclusion: Segregation of different contextual characteristics of neighborhood had different effects on health outcomes. Studying segregation of social, economic, and demographic factors, especially in communities, which are racially homogenous, might reveal new insights into dissimilarities in health.